Assessment of Settlement Area Development in Jember Regency Area Based on Multitemporal LANDSAT 8 OLI-TIRS Data - Bowo Eko Cahyono; Inas Alfiyatul Umniyah (Department of Physics, Sebelas Maret University, 2025)
Jember is a regency in the province of East Java-Indonesia, experiencing residential or settlement area growth because of increasing population as the main trigger for land use changing. Monitoring the development of settlement areas is important for regional and urban planning. Remote sensing technology provides fast and efective methods of classifying land use and land cover for regional aea, so monitoring the development of settelemnent area can be identified easily. This study aims to determine the classification of land use and analyse the distribution or evelopment of settlement area in the Jember District based on LANDSAT 8 OLI-TIRS data for the year of 2013, 2015, 2017, 2019 and 2021. The classification was conducted by supervised classification method using a random forest algorithm. The land use is divided into six classes namely vegetation, water body, settlement, bush grass, open land and paddy field. The results showed that settlement area continues to increase every year, meanwhile the area of vegetation, water bodies, bush grass, open land and paddy fields varies every year. The distribution of settlement area in each sub-district showed that the largest area of settlements occur in Ambulu sub-district with 1,447 ha in 2013, 4,064 ha in 2019, and 3,215 ha in 2021. The other years that are 2015 and 2017, Wuluhan sub-district was detected as the largest area of settlement which are 2,950 ha in 2015 and 2,291 ha in 2017. However, this number of settlement area distribution does not really reflect the level of housing density in each sub-district. Thus, the housing density was calcuated by dividing the settlement area to the sub-district area. It found that the highest settlement density in 2021 is located in Kaliwates sub-district with a percentage of 48%, followed by Sumbersari at 44%, Balung at 31%, Ambulu at 30%, and Umbulsari at 29%.